The Countermeasures Efforts of Illegal Transshipment Impact as a Transnational Crime - Husni Mubaroq; Muhammad Haidir Syah Putra (Pancasila and Law Review, 2022)
The impacts and disadvantages of transhipment which even threatens sustainable development shows that transhipment can be identified as a transnational crime. On the one side, there is a need for legal countermeasures for the transshipment crimes in Indonesia so it does not occur again. But on the other side, transshipment actually becomes a necessity because fish landing mostly take time so that the fish are not fresh. In addition, the transshipment countermeasures also has some obstacles because there is no agency or institution with a special task of supervising and taking action against waters crimes in Indonesian in full authority to tackle transhipment. The problem that will be discussed in this article is how is transhipment related to transnational crime? And what is the countermeasures framework for dealing transhipment related to transnational crime? The research results showed that transshipment has been regulated in international law and national law. However, transhipment can be classified as a transnational crime because it fulfills the elements of a transnational crime and it is related to other transnational crimes. So there is a recommendation for a countermeasures framework of transhipment crime as a transnational crime, namely by establishing cooperation between the central and regional governments in the field of marine and fisheries. Then other recommendations related to handling fisheries crime cases such as transhipment can be carried out through a restorative justice mechanism that charges criminals to compensate for losses and recover fish resources due to their crimes.